Pembangunan dan Pengembangan Strategi Obyek Wisata Air Terjun Kanto Lampo di Kelurahan Beng Kabupaten Gianyar - Wetarani, Ni Putu Karnhura; Yasintha, Putu Nomy; Putri Wirantari, I Dewa Ayu (CITIZEN CHARTER, 2019)
ABSTRACT The Kanto Lampo Waterfall Tourism Object is the Tourism Potential of Gianyar Regency. Development strategies began to be taken by Tourism Object Managers such as the establishment of Tourism Object Management Board and the Construction of Tourism Object supporting facilities. The indicators used to dissect this research are the Tourism Development Phase indicators, (1) Exploration, (2) Involvement, (3) Development, (4) Consolidation, (5) Stagnation, (6) Rejuvenation. The results of this study indicate that the five phases of the development indicator have been included in the Development of Tourism Object Strategie. This study produced a recommendation in the form of a New Village Tourism Object Development Model to provide the right strategy to increase the potential of a Tourism Object. Keywords: Kanto Lampo Waterfall Tourism Object, Tourism Object Development Strategy, Tourism Development.